(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Radiation factors-exposure dose rate of gamma-radiation, specific effective activity (Aeff), specific activity of radionuclides, equivalent equilibrium activity of radon (EEA), activity of long-lived radionuclides (LLR), radon flux density (RFL), coefficients of radioactive equilibrium etc., and methods for definition of their significance in Navoi industrial region are actual tasks of radioecology. Values of radiation factors are regulated by normative international documents and documents of the Republic of Uzbekistan. The established norms of radiation safety are monitored in industrial and settlements as well as in the adjacent areas of the so-called observation points [1,7]. Exposure dose values are estimated by means of radiation analysis of soil, air, plants, drinking, waste and underground water in observation points of adjacent territories to sources of environmental contamination [2-6]. On the basis of the performed researches it is possible to determine -238U, 232Th, 226Ra, 40K concentrations in soil, water and technological products as well as to find the forms of elements in liquid phase using nuclear filters and to determine the fractional composition of uranium-containing solid fractions in gas emissions using nuclear filters. Based on the value of the enrichment factor of chemical elements in the soil, we can find a pattern of localization of man-made chemical elements in some areas of the studied areas of uranium production. On the basis of the studies conducted to determine the migration of chemical elements in the groundwater we can predict the possible values of groundwater contamination in the area of uranium and gold mining plants.The main component of the values of environmental exposure doses are radioactive pollutants and their compound in the soil, air, plants, drinking, waste and groundwater [8-18].